1995
DOI: 10.1002/bit.260480103
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Penicillium chrysogenum physiology in submerged cultures by color and monochrome image analysis

Abstract: Although filamentous microorganisms are widely used in industrial fermentation processes, their growth and differentiation are not yet fully understood, because their biomass is structured, and therefore difficult to describe and to quantify. This lack of appropriate tools can hinder the optimization and control of the fermentation. A quantitative image analysis method was therefore developed for characterizing the physiology of the penicillin-producing mold Penicillium chrysogenum. This method is based on a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…An exception is the work of Paul and Thomas (1996) in which image analysis was used to characterize the cellular differentiation of P. chrysogenum for use in the estimation of model parameters. Vanhoutte et al (1995) demonstrated the potential of automated image analysis by using multiple staining of hyphal elements to distinguish between six different hyphal zones in P. chrysogenum, ranging from the active apical regions to the most distal dead regions, but the results obtained were not used for any modeling purposes.…”
Section: Introductionmentioning
confidence: 99%
“…An exception is the work of Paul and Thomas (1996) in which image analysis was used to characterize the cellular differentiation of P. chrysogenum for use in the estimation of model parameters. Vanhoutte et al (1995) demonstrated the potential of automated image analysis by using multiple staining of hyphal elements to distinguish between six different hyphal zones in P. chrysogenum, ranging from the active apical regions to the most distal dead regions, but the results obtained were not used for any modeling purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Two thresholds are defined to detect the three regions of interest, that enable to define three physiological states: growing, non-growing (cytoplasm with vacuoles < 30 mm 3 ), degenerated (cytoplasm with vacuoles > 30 mm 3 ). A simple monochrome CCD-camera can be used, which was not the case for the staining procedure developed for the same microorganism by Vanhoutte et al [169]: a mixture of Methylene Blue and Ziehl Fuschin takes various hues (orange, gray, purple), the subtle changes of which can be picked up correctly only by a 3-CCD color camera. Six physiological states were defined: growing, four states with increased degree of differentiation, dead, and the physiological status of hyphae could be monitored along the culture.…”
Section: ) Pellet Convex Area -Core Convex Areamentioning
confidence: 98%
“…Fluorescent stains coupled with image analysis have been used in the works of Vanhoutte et al [39], Agger et al [40], Wongwicharn et al [41], Hamanaka et al [42] and Amanullah et al [13]. Vanhoutte et al [39] using a differential staining procedure and color image analysis in studies on the growth and differentiation of P. chrysogenum showed and quantified six physiological states: growing material (zone 1), three differentiated states characterized by increased granulation (zones 2,3,4), a highly vacuolated state (zone 5) and dead segments empty of cytoplasm (zone 6). Ager et al [40] used a double staining procedure (calcofluor and DiOC6), fluorescence microscopy and automatic image analysis in studies on the morphology of A. oryzae.…”
Section: Identification Of the Metabolically Active Fraction Of The Mmentioning
confidence: 99%